Application of the Demonstration Method Using Original Media to Improve Students' Skills in Mathematics Class II Elementary School - Magdalena, Sari Maria (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Many students get very low formative test results in mathematics. The demonstration method uses original media in mathematics, helping students play an active role in learning. The goal is that learning is fun, understanding is not abstract, and student learning outcomes are increasing. The research implementation consisted of two cycles and each cycle included four stages, namely planning, action, observation and reflection. Cycle I on Wednesday 18 May 2022 and Cycle II on Wednesday 25 May 2022. The results of the analysis of formative test scores before improvement, after improvement in cycle I, improvement in cycle II, there is an increase. The discussion before the cycle failed, cycle I increased, cycle II was maximally successful. the conclusion that the application of demonstration methods using real objects can improve students' skills in Mathematics. The advice given, the application of demonstration methods using original media such as interesting objects and according to subject matter can arouse student enthusiasm for learning.